1983
DOI: 10.1002/j.1460-2075.1983.tb01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock puff 93 D from Drosophila melanogaster: accumulation of a RNP-specific antigen associated with giant particles of possible storage function.

Abstract: The monoclonal antibody P11 is directed against a 38 000 dalton protein of Drosophila melanogaster. On polytene chromosomes this protein is present in a subset of the RNA polymerase II‐containing loci. Here we show by density centrifugation and enzyme‐linked immunosorbent assay tests that the P11 antigen is part of nuclear ribonucleoprotein (RNP) complexes. Indirect immunofluorescence shows that, after prolonged heat‐shock, the P11 antigen is present only in the heat‐shock puff 93 D. Identical distribution pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…In the course of assaying for targeting of Sxl proteins to a transgene driven by the hs83 promoter, the surprising result was noted that besides accumulating at the transgene insertion site, Sxl proteins also accumulated at the heat shock 93D locus following prolonged heat shock. This chromosomal site has previously been shown to accumulate a known hnRNP packaging protein upon heat shock (P11, equivalent to hrp36) (19,36). To our knowledge, Sxl is the first example of a regulatory RNA-processing factor shown to accumulate at 93D.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the course of assaying for targeting of Sxl proteins to a transgene driven by the hs83 promoter, the surprising result was noted that besides accumulating at the transgene insertion site, Sxl proteins also accumulated at the heat shock 93D locus following prolonged heat shock. This chromosomal site has previously been shown to accumulate a known hnRNP packaging protein upon heat shock (P11, equivalent to hrp36) (19,36). To our knowledge, Sxl is the first example of a regulatory RNA-processing factor shown to accumulate at 93D.…”
Section: Resultsmentioning
confidence: 84%
“…The transcript also lacks long poly(U) tracts (20,31,52), suggesting that Sxl may not be directly binding to 93D transcripts but instead may be interacting with other proteins. Ultrastructural analyses of 93D puffs following heat shock show large granules containing P11 (hrp36) protein, suggesting that nuclear RNA-binding proteins may be assembled into large RNP aggregates during heat shock (19). The 93D locus may thus, among other functions, serve as a storage site for the pre-mRNA packaging and processing machinery under stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Each is the only puffin the genome that is also induced by benzamide and by colchicine (3,4). During heat shock each of these puffs contains distinctive large ribonucleoprotein particles that share antigenic determinants not seen on other heat shock puffs (5). The unusual characteristics shared by these two puffs strongly suggest that the function of the locus is conserved in spite of the divergence at the nucleotide level.…”
mentioning
confidence: 87%
“…We analyzed the pattern of binding of wild-type and mutant HRB87F/hrp36 proteins to sites of transcription on polytene chromosomes+ Previous studies have established that the protein has a wide distribution pattern during normal growth conditions (Amero et al+, 1992;Matunis et al+, 1993), but a single strong site of accumulation (on heat-shock puff 93D) immediately after heat shock (Dangli et al+, 1983;Hovemann et al+, 1991;Zu et al+, 1996)+ These two chromosomal staining patterns are shown for our epitope-tagged wild-type HRB87F/hrp36 protein in Figures 4A (heat shock) and 5A (normal growth)+ We asked which domains of the protein are responsible for these two very different native RNA binding patterns+…”
Section: Rbd-2 and The Grd Reproduce The Distribution Pattern Of The mentioning
confidence: 99%